2001
DOI: 10.1104/pp.126.3.1105
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis Mutant Tolerant to Lethal Ultraviolet-B Levels Shows Constitutively Elevated Accumulation of Flavonoids and Other Phenolics

Abstract: The isolation and characterization of mutants hypersensitive to ultraviolet (UV) radiation has been a powerful tool to learn about the mechanisms that protect plants against UV-induced damage. To increase our understanding of the various mechanisms of defense against UVB radiation, we searched for mutations that would increase the level of tolerance of Arabidopsis plants to UV radiation. We describe a single gene dominant mutation (uvt1) that leads to a remarkable tolerance to UVB radiation conditions that wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
211
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(227 citation statements)
references
References 37 publications
9
211
0
3
Order By: Relevance
“…Flavonoids and anthocyanins were extracted according to Bieza & Lois (2001). One hundred milligrams of leaves were grounded in liquid N2 and flavonoids were extracted for 2 h at 4°C with 400 mL of methanol, centrifuged for 10 min at 10 000 g, and the supernatant was quantified at A330 nm in an Ultrospec 1100 pro spectrophotometer (Amersham Biosciences, Cambridge, UK).…”
Section: Flavonoid and Anthocyanin Quantificationmentioning
confidence: 99%
“…Flavonoids and anthocyanins were extracted according to Bieza & Lois (2001). One hundred milligrams of leaves were grounded in liquid N2 and flavonoids were extracted for 2 h at 4°C with 400 mL of methanol, centrifuged for 10 min at 10 000 g, and the supernatant was quantified at A330 nm in an Ultrospec 1100 pro spectrophotometer (Amersham Biosciences, Cambridge, UK).…”
Section: Flavonoid and Anthocyanin Quantificationmentioning
confidence: 99%
“…UV-B photons generate photoproducts in DNA and can also directly damage proteins, lipids, and RNA (Britt, 1996;Gerhardt et al, 1999;Casati and Walbot, 2004). Thus, plants have evolved mechanisms of protection (Stapleton and Walbot, 1994), repair (Waterworth et al, 2002;Bergo et al, 2003), and avoidance (Mazza et al, 2000;Bieza and Lois, 2001). Although UV-B photon perception and signal transduction are largely unknown (Brosche and Strid, 2003;Frohnmeyer and Staiger, 2003;Ulm and Nagy, 2005), it was recently shown that the basic domain/Leu zipper transcription factor long hypocotyl 5 (HY5), first identified as a factor for normal growth in visible light, is also an important participant in the long-wavelength (300-315 nm) UV-B light-induced signal transduction cascade in Arabidopsis (Ulm et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…No caso específico dos flavonóides, estes são acumulados principalmente em tecidos superficiais (tais como epiderme, subepiderme, pêlos, cutícula e material epicuticular) e utilizados pela planta como filtros UV, pois absorvem radiação UV-B sem alterar a radiação fotossinteticamente ativa 101,111,112 . Além disso, também podem atuar como "radical-scavengers" e antioxidantes 108,113 .…”
Section: Radiação Ultravioletaunclassified